The good daughter - Burt, Alexandra (Berkley, 2017)
"From the author of Remember Mia comes the tale of a young woman in search of her past, and the mother who will do anything to keep it hidden... What if you were the worst crime your mother ever committed? Dahlia Waller's childhood memories consist of stuffy cars, seedy motels, and a rootless existence traveling the country with her eccentric mother. Now grown, she desperately wants to distance herself from that life. Yet one thing is stopping her from moving forward: she has questions. In order to understand her past, Dahlia must go back. Back to her mother in the stifling town of Aurora, Texas. Back into the past of a woman on the brink of madness. But after she discovers three grave-like mounds on a neighboring farm, she'll learn that in her mother's world of secrets, not all questions are meant to be answered.."